STRESS FACTORS AND PREFERRED COPING STRATEGIES OF PARTICIPANTS IN XXXI BULGARIAN ANTARCTIC EXPEDITION - Tatiana Iancheva; Doychin Boyanov; Nikolay Panayotov (Scientific Publishing House. NSA Press, 2023)
The interest in behavior, psychological changes, stress coping strategies, and polar expedition members' functioning has been growing in recent years. The third group of the XXXI Bulgarian Antarctic expedition in Livingston Island at the beginning of 2023 included participants from three fields - scientists, logisticians, and builders. Participants' activities are greatly dependent on extreme environmental conditions. The aim of this study was to examine the sensation-seeking need, major stress factors, and preferred stress coping strategies of the participants in XXXI Bulgarian Antarctic expedition in Livingston Island. The research was done among 28 participants from XXXI Bulgarian Antarctic expedition, aged between 30 and 71 years. To fulfill the aim of the research, we used: 1) Methodology for researching psychic instability and sensation seeking, adapted by Velichkov & Radoslavova, 2005; 2) Coping Orientations to Problems Experienced scale - COPE - 1, Carver et al., 1989, adapted for Bulgarian conditions (Georgiev et al., 2003); 3) Methods for researching stress sources among participants in Antarctic expeditions. The results showed that the subscale functional impulsivity had the highest values. It was followed by the subscales of sensation seeking and dysfunctional impulsivity. The factor Interpersonal relationships and an abrupt change in the familiar environment had the highest values as a stress source. The emotional coping strategies were domineering, followed by the active coping strategy. The strategy of Cognitive and Emotional disengagement had the lowest values. There were significant differences from the results obtained from previous Bulgarian expeditions. The results can help adaptation and adequate prevention to decrease participants' psychological stress.